Legends of the North Cascades : a novel - Evison, Jonathan (Algonquin Books of Chapel Hill, 2021)
"After his wife's death, a man brings his young daughter to live in a cave he has found in the Cascade mountains. Once there, his daughter begins to sense the presence of other people in the cave, a mother and son who retreated there during the last ice age in an effort to survive"--